Kekuatan Hukum Penyelesaian Sengketa Waris Melalui Mediator Tokoh Masyarakat di Desa Wonosalam Kecamatan Wonosalam Kabupaten Demak - Mahrus, Ahmad Falih (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This article is a field research to answer the role of community leaders as mediators in the settlement of inheritance disputes in Wonosalam, Demak and how the legal power of resolving inheritance disputes through mediator community leaders in Wonosalam, Demak. Research data are collected through interviews and observations, then are analyzed with descriptive analytical techniques with inductive thought pattern. Wonosalam community leaders have an important role in the settlement of inheritance disputes, namely as a mediator, including: opening and leading the mediation process, explaining and determining the heirs' parts, providing the best advice and solutions, deciding and determining what has been agreed by the parties to the dispute, preventing the emergence of even bigger disputes, and still maintaining harmony and harmony in social life. The results of the settlement of inheritance disputes through mediators of community leaders in Wonosalam do not have an enforceable legal force, because they are not confirmed by making a peace certificate or a peace agreement letter, which is contained in: article 27 of the Supreme Court Regulation No. 1 of 2016 concerning Mediation Procedures and article 1851 Civil Code. Nevertheless, the determination of community leaders as mediators in the settlement of inheritance disputes is obeyed and implemented by the people of Wonosalam. [Artikel ini adalah hasil penelitian lapangan untuk menjawab bagaimana peran tokoh masyarakat sebagai mediator dalam penyelesaian sengketa waris di Desa Wonosalam Kecamatan Wonosalam Kabupaten Demak dan bagaiamana kekuatan hukum penyelesaian sengketa waris melalui mediator tokoh masyarakat Desa Wonosalam Kecamatan Wonosalam Kabupaten Demak. Data penelitian dihimpun melalui wawancara dan observasi, dianalisis dengan teknik deskriptif analitis dengan pola pikir induktif. Tokoh masyarakat Desa Wonosalam memiliki peran penting dalam penyelesaian sengketa waris, yaitu sebagai mediator, diantaranya: membuka dan memimpin proses mediasi, menjelaskan dan menentukan bagian-bagian ahli waris, memberikan nasihat dan solusi yang terbaik, memutuskan dan menetapkan apa yang telah disepakati para pihak yang bersengketa, mencegah timbulnya sengketa yang lebih besar lagi, dan tetap menjaga kerukunan dan keharmonisan dalam hidup bermasyarakat. Hasil penyelesaian sengketa waris melalui mediator tokoh masyarakat di Desa Wonosalam tersebut tidak mempunyai kekuatan hukum yang eksekutorial, karena tidak dikukuhkan dengan pembuatan akta perdamaian ataupun surat perjanjian perdamaian sesuai pasal 27 Peraturan Mahkamah Agung Nomor 1 Tahun 2016 tentang Prosedur Mediasi dan pasal 1851 KUH Perdata. Meski demikian, ketetapan tokoh masyarakat sebagai mediator dalam penyelesaian sengketa waris tersebut dipatuhi dan dilaksanakan oleh masyarakat Desa Wonosalam.]